The role of mental health professionals in the climate crisis: an urgent call to action. (4th July 2022) - Li, Ching; Lawrance, Emma L.; Morgan, Gareth; Brown, Richard; Greaves, Natalie; Krzanowski, Jacob; Samuel, Sophie; Guinto, Renzo R.; Belkin, Gary
Abstract: The climate and ecological crisis will constitute the defining public health challenge of the twenty-first century, posing an unprecedented global threat to all determinants of health, and to healthcare delivery systems. We believe that mental health professionals have a crucial role to play in responding to this crisis. Whilst responding to the mental health consequences of the climate crisis will remain a key role for us as mental health professionals, we argue that our remit goes beyond this, and should include advancing public understanding of the climate crisis, highlighting its impact on physical and mental wellbeing, and advocating for systemic changes to limit its impending harms. This paper is an urgent call to action for all mental health professionals to take up a role in the context of the climate and ecological crisis. This paper will describe the relationship between mental health and climate change, and frame it within wider systemic and conceptual frameworks. It will demonstrate that as mental health professionals we are well placed to act as leaders of change—arguing that we have a duty to do so—and suggest actions that can be implemented depending on interests, skill sets and opportunities.